Inhibition of Cdk5 increases osteoblast differentiation and bone mass and improves fracture healing - Mubashir Ahmad; Benjamin Thilo Krüger; Torsten Kroll; Sabine Vettorazzi; Ann-Kristin Dorn; Florian Mengele; Sooyeon Lee; Sayantan Nandi; Dilay Yilmaz; Miriam Stolz; Naveen Kumar Tangudu; David Carro Vázquez; et al. (Bone Research, 2022)
Abstract Identification of regulators of osteoblastogenesis that can be pharmacologically targeted is a major goal in combating osteoporosis, a common disease of the elderly population. Here, unbiased kinome RNAi screening in primary murine osteoblasts identified cyclin-dependent kinase 5 (Cdk5) as a suppressor of osteoblast differentiation in both murine and human preosteoblastic cells. Cdk5 knockdown by siRNA, genetic deletion using the Cre-loxP system, or inhibition with the small molecule roscovitine enhanced osteoblastogenesis in vitro. Roscovitine treatment significantly enhanced bone mass by increasing osteoblastogenesis and improved fracture healing in mice. Mechanistically, downregulation of Cdk5 expression increased Erk phosphorylation, resulting in enhanced osteoblast-specific gene expression. Notably, simultaneous Cdk5 and Erk depletion abrogated the osteoblastogenesis conferred by Cdk5 depletion alone, suggesting that Cdk5 regulates osteoblast differentiation through MAPK pathway modulation. We conclude that Cdk5 is a potential therapeutic target to treat osteoporosis and improve fracture healing.